2018
DOI: 10.1093/pcp/pcy061
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Compounds that Affect Stomatal Movements

Abstract: Regulation of stomatal aperture is essential for plant growth and survival in response to environmental stimuli. Opening of stomata induces uptake of CO2 for photosynthesis and transpiration, which enhances uptake of nutrients from roots. Light is the most important stimulus for stomatal opening. Under drought stress, the plant hormone ABA induces stomatal closure to prevent water loss. However, the molecular mechanisms of stomatal movements are not fully understood. In this study, we screened chemical librari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 73 publications
0
57
0
1
Order By: Relevance
“…Different rankings of our study species with respect to the kinetics of light‐induced stomatal opening versus VPD‐induced stomatal closure may reflect differences in the mechanisms involved. Stomatal responses to light depend on activation of plasma membrane H + ‐ATPase (Toh et al, ), sucrose degradation, and glycolysis and the tricarboxylic acid cycle (Medeiros et al, ). However, the short‐term stomatal response to VPD appears to be mediated by up‐regulation of abscisic acid biosynthesis (McAdam & Brodribb, ) or the sensitivity of ion transporters (Pantin & Blatt, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different rankings of our study species with respect to the kinetics of light‐induced stomatal opening versus VPD‐induced stomatal closure may reflect differences in the mechanisms involved. Stomatal responses to light depend on activation of plasma membrane H + ‐ATPase (Toh et al, ), sucrose degradation, and glycolysis and the tricarboxylic acid cycle (Medeiros et al, ). However, the short‐term stomatal response to VPD appears to be mediated by up‐regulation of abscisic acid biosynthesis (McAdam & Brodribb, ) or the sensitivity of ion transporters (Pantin & Blatt, ).…”
Section: Discussionmentioning
confidence: 99%
“…Stomatal responses to light depend on activation of plasma membrane H + -ATPase (Toh et al, 2018), sucrose degradation, and glycolysis and the tricarboxylic acid cycle (Medeiros et al, 2018).…”
Section: Stomatal Regulation Of Midday Leaf and Stem ψ Along A Specmentioning
confidence: 99%
“…Since ABA is a small molecule, it would be intriguing to know if other small molecules can control this system. Here, Toh et al (2018) report a comprehensive screening of chemical libraries to identify compounds that affect stomatal movements and the underlying molecular mechanisms. They showed that stomatal closing compounds (SCLs) suppress light-induced stomatal opening, and that SCL1 and SCL2 suppress light-induced stomatal opening at least in part by inhibiting blue light-induced activation of plasma membrane H + -ATPase, which is a key enzyme for stomatal opening.…”
Section: Chemical Screening For Stomatal Movementsmentioning
confidence: 99%
“…Recently, we isolated compounds that regulate stomatal movements (stomatal closing compounds; SCLs) in a chemical screen focussed on stomatal apertures 9 . Limiting to include only chemicals for quantification that altered stomatal aperture greatly enhanced the screening throughput to 150 compounds per day, which resulted in the successful identification of 9 candidates from over 20,000 chemicals.…”
mentioning
confidence: 99%
“…Our calculated IC 50 of ABA was close to a previously reported value, 0.36 µM 9 . Next, we reanalysed 715 images acquired from our recent chemical screen to identify compounds that alter stomatal movement 9 . In addition to the stomatal apertures, we also calculated the percentage of open, partially open, and closed stomata classified by the CNN.…”
mentioning
confidence: 99%